Prayer in America: A Detailed Analysis of the Various Dimensions of Prayer - Froese, Paul (Journal for the scientific study of religion, 2022)
Despite prayer's central role in religious life, quantitative research on prayer typically focuses on its frequency without regard to the total amount, to why, to whom, or for what a person might be praying, nor how people feel when they pray. In this paper, we broaden our understanding of the prayer practices of American adults by focusing on their (1) quantity of prayer, (2) style of prayer, (3) purpose of prayer, (4) prayer target, and (5) emotional state during prayer. Using the Baylor Religion Survey (N = 1248), collected January–March 2021, we present frequencies and findings from factor analyses of key conceptual dimensions of prayer and then indicate how prayer dimensions correlate with each other and vary by basic religion and demographic variables. Our findings provide a detailed picture of these relationships and also provide researchers with best practices in how to measure the various dimensions of prayer in future studies.